Photochemical Behavior of Multicomponent Polymeric-based Materials - Rosu, Dan; Visakh P. M. (Advanced Structured Materials, 2016)
This book offers in-depth insights into the photochemical behavior of multicomponent polymeric-based materials, with a particular emphasis on the photodegradation and photostabilization of these materials. Studying various classes of materials bases such as polysaccharides, wood, synthetic polymers, rubber blends, and nanocomposites, it offers a valuable reference source for graduate and postgraduate students, engineering students, research scholars and polymer engineers working in industry.